Experimental Diagnostic of Cavitation Flow in the Centrifugal Pump Under Various Impeller Speeds Based on Acoustic Analysis Method - AL-OBAIDI, Ahmed Ramadhan (Archives of Acoustics, 2023)
Condition monitoring in a centrifugal pump is a significant field of study in industry. The acoustic method offers a robust approach to detect cavitations in different pumps. As a result, an acoustic-based technique is used in this experiment to predict cavitation. By using an acoustic technique, detailed information on outcomes can be obtained for cavitation detection under a variety of conditions. In addition, various features are used in this work to analyze signals in the time domain using the acoustic technique. A signal in the frequency domain is also investigated using the fast Fourier method. This method has shown to be an effective tool for predicting future events. In addition, this experimental investigation attempts to establish a good correlation between noise characteristics and cavitation detection in a pump by using an acoustic approach. Likewise, it aims to find a good method for estimating cavitation levels in a pump based on comparing and evaluating different systems.